PENGARUH SOSIALISASI POLITIK TERHADAP PARTISIPASI PEMILIH PEMULA DI PULAU JAWA MENJELANG PEMILU 2024 - Gaynell, Najla Eltira; Bakry, Gema Nusantara (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
Political socialization is the process of instilling political values in individuals and groups, which will later be useful and can form a culture in society. The role of political socialization is quite important in determining the political choices of an individual or group, especially when approaching the general election. In the 2024 general election, the most votes were obtained from the younger generation. When viewed from its territory, Java Islandis the island with the largest DPT in Indonesia among the total national voters in 38 provinces. The purpose of this study is to see how much influence political socialization has on the political participation of new voters on Java Island ahead of the 2024 general election. This study uses social learning theory to determine the effect of political socialization on political participation. The approach to this research is quantitative, with a survey method. The data collection technique was carried out by distributing a Likert scale questionnaire (5 points) to new voters domiciled in Java Island, Indonesia, with a non probability sampling type of convenience sampling technique and obtaining a sample size of 395. The questionnaire was distributed via social media to collect primary data. Data analysis was car ried out by processing and grouping the data that had been collected from respondents. In the dataanalysis, validity, reliability, and regression tests were also carried out to determine the feasibility of the instrument, the consistency of measurement results, and the relationship between the dependent variable and the independent variable. The results of the study showed that there was an influence between political socializationand the participation of new voters on Java Island ahead of the 2024 election.